Stability analysis of slopes with a potential of slide-head-toppling failure. (December 2018) - Amini, Mehdi; Sarfaraz, Hassan; Esmaeili, Kamran
Abstract: Toppling is a mode of slope instability that may occur in a wide range of layered or blocky rock masses. If this instability is caused by some natural or man-made external factors, it is termed a secondary toppling failure. One of the important modes of toppling instability is the slide-head-toppling failure. When a layer of soil or weak rock is overlaid by a blocky or layered rock mass, the combination of a toppling failure in the rock at the top and a circular sliding in the soil or weak rock in the bottom leads to this hybrid failure. The mechanism of this hybrid failure is extremely complicated and it may occur in some special geological conditions in civil engineering and mining projects. In this paper, the mechanisms of toppling failures, in general, and the mechanism of slide-head-toppling failure, in particular, are presented and described. Then, the outcomes of seven physical models, which were constructed with base friction materials and conducted under static loading conditions by a tilting table apparatus, are summarized to investigate this hybrid failure mechanism. Subsequently, a new step by step theoretical approach is proposed for assessment of this failure mode and a typical example is analyzed to better demonstrate the results. Finally, the results of the physical modeling are compared with the outcomes of the proposed theoretical method and an existing analytical approach. This comparison shows that there are acceptable agreements between the physical and analytical results. Hence, both proposed and existing analytical approaches can be used for the analysis of the slide-head-toppling slope failure.